Social problem-solving workation through collaboration between local regions and urban companies: the case of Kamaishi in Japan - Matsushita, Keita (Frontiers in Sustainable Tourism, 2024)
This study analyzed a social problem-solving workation in Kamaishi, Japan, focusing on the "hitohada nugu" experience, a cross-boundary and other-oriented contribution and relationshipbuilding experience. The results of interviews with stakeholders of the work experience, including company managers and participants, intermediaries in the host local community, and government officials, as well as a questionnaire survey of all participants, indicated that employees who participated in the program learned and grew through their inexperience in Kamaishi, which was different from their work experience. On the other hand, the local community and companies that plan and operate the program face a dilemma in explaining the effects of the workation on the company's business, the solution to local issues, and the learning and growth of employees. companies with 10-100 employees or less. By region, 33.7% of companies were located in the Tokyo area (Tokyo, Kanagawa, Saitama, and Chiba prefectures), 20.0% in the Osaka area (Osaka, Hyogo, Kyoto, and Nara prefectures), and 16.2% in the Nagoya area (Aichi, Gifu, and Mie prefectures), the next largest economy. These results indicate that most teleworkers are full-time employees of large companies in urban areas, especially in the Tokyo area (Persol Research and Consulting, 2023a). These findings indicate that the acceptance of work in large urban companies is crucial for creating a related population.This study aims to clarify how the "Hitohada nugu" experience builds participants' attachment to the organization and region and their learning and growth. "Hitohada nugu" is a Japanese expression. Hitohada nugu" is an expression derived from the action of rolling up the sleeves of a kimono when doing heavy lifting, and refers to enthusiastic help for others or to a friendly agreement to participate in a project. This study shows the benefits and dilemmas of a problem-solving work experience program that contributes to the community from the perspective of the "Hitohada nugu" experience and how it should be designed. Among affiliative nomads in Japan, practitioners of this local problem-solving workation will play a significant role.